Recent excavations in Israel: studies in Iron Age archaeology ; [papers from the 1985 American Schools of Oriental Research Symposium. Annual meeting held November 22-26, 1985, in Anaheim, California] - Gitin, Seymour (The annual of the American Schools of Oriental Research, 1989)
Essays from the 1985 ASOR Symposium entitled "The Impact of Recent Archaeological Excavations and Publications on the History of Ancient Israel."